2018
DOI: 10.1002/jcp.26788
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen inhibits osteoclasts formation and bone resorption via microRNA‐27a targeting PPARγ and APC

Abstract: Inhibition of osteoclasts formation and bone resorption by estrogen is very important in the etiology of postmenopausal osteoporosis. The mechanisms of this process are still not fully understood. Recent studies implicated an important role of microRNAs in estrogen‐mediated responses in various cellular processes, including cell differentiation and proliferation. Thus, we hypothesized that these regulatory molecules might be implicated in the process of estrogen‐decreased osteoclasts formation and bone resorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…In postmenopausal osteoporosis, estrogen therapy effectively prevents bone loss ( 39 ). Emerging evidence has demonstrated that estrogen exhibits an inhibitory role in osteoclast formation and enhances osteoblast function ( 40 , 41 ). During estrogen-decreased osteoclast differentiation, miR-27a remarkably enhances the inhibitory effect of estrogen ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In postmenopausal osteoporosis, estrogen therapy effectively prevents bone loss ( 39 ). Emerging evidence has demonstrated that estrogen exhibits an inhibitory role in osteoclast formation and enhances osteoblast function ( 40 , 41 ). During estrogen-decreased osteoclast differentiation, miR-27a remarkably enhances the inhibitory effect of estrogen ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has demonstrated that estrogen exhibits an inhibitory role in osteoclast formation and enhances osteoblast function ( 40 , 41 ). During estrogen-decreased osteoclast differentiation, miR-27a remarkably enhances the inhibitory effect of estrogen ( 40 ). In addition, following treatment with antiosteoporotic agents, serum miR-27a levels are significantly reduced in postmenopausal women ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, T-fimbrin is an inhibitor of sealing zone formation and its deletion increases bone resorption (Neugebauer et al, 2018). Finally, APC is involved in the association between vimentin intermediate filaments and microtubules (Leduc et al, 2015) and as described above, APC appears important in organizing the podosome belt and for bone resorption (Guo et al, 2018;Matsumoto et al, 2013). However, the specific functions of APC and vimentin in osteoclasts are unknown.…”
Section: Intermediate Filaments and Septinsmentioning
confidence: 96%
“…Both EB1 and APC participate in actin-microtubule crosstalk (Dogterom et al, 2019). In osteoclasts, EB1 is required for podosome belt formation (Biosse Duplan et al, 2014) and indirect evidence suggest that APC has an important role at the podosome belt as well as in bone resorption (Guo et al, 2018). Besides AKT, Dock5 also regulates microtubule acetylation and GSK3β activity in osteoclasts (Fig.…”
Section: Actin and Microtubule Crosstalk At The Podosome Beltmentioning
confidence: 97%
“…Inhibiting the activity of miR-23a-3p can increase the expression level of LRP5 and thus increase the differentiation of osteoblasts. As a target of miR-27a, APC is inhibited, and miR-27a increases β-catenin to activate the WNT signaling pathway (Guo et al, 2018). Other studies have shown that miR-142-3p regulates APC activation of Wnt/β-catenin Signaling, while Hu et al (2016) have demonstrated that miR-142-3p can directly inhibit the activity of β-catenin in Wnt/β-catenin Signaling.…”
Section: Pathway-level Analysismentioning
confidence: 99%